PERKAWINAN ADAT MASYARAKAT SUKU PADOE DI DESA WAWONDULA KECAMATAN TOWUTI KABUPATEN LUWU TIMUR PROVINSI SULAWESI SELATAN - Meylan Cristi Emilia Sepena (HOLISTIK, Journal of Social and Culture, 2023)
Indonesia is a country with diverse cultures in it. Preserving culture is important for life, namely as a principle of the nation, an identification of a foreign country, the identity of the nation, and a means of learning. The culture of the Indonesian nation is still carried out by its supporting communities. South Sulawesi is a province in Indonesia that is diverse in ethnic groups. One of the tribes that inhabit the South Sulawesi area is the Padoe tribe. The Padoe tribe comes from the noble values of the people in the East Luwu Regency area, Towuti District. The Padoe tribe has many unique rules and traditions that can still be found today. One of them is traditional marriage which has a philosophical meaning, namely appreciation (Mompelangkai) which means arranging morals, manners and ethics in marriage, as well as appreciation or acceptance of parents and their families. The Padoe tribe has its own ideal marriage where the traditional Padoe marriage is not dependent on other marriages because it is special for people who are oriented or claim to be Padoe people as well as ancestors of the Padoe people. So that Padoe traditional marriage is binding in the sense of marriage for generations of Padoe people. Marriage according to the traditional order of padoe consists of proposing (Mosoro Pesikeno) and marriage (Mesombori). After the implementation of the series of customary marriages is completed, it is continued with religious marriages and state marriages. Keywords: traditional ceremony, traditional marriage, padoe tribe